Is the use of ACE inb/ARBs associated with higher in-hospital mortality in Covid-19 pneumonia patients? - Murat Selçuk; Tufan Çınar; Muhammed Keskin; Vedat Çiçek; Şahhan Kılıç; Behruz Kenan; Selami Doğan; Süha Asal; Nuran Günay; Ersin Yıldırım; Ümran Keskin; Ahmet Lütfullah Orhan (Clinical and Experimental Hypertension, 2020)
Introduction The present research aimed to determine the relation between the use of angiotensin-converting enzyme inhibitors (ACE inh) and angiotensinogen receptor blockers (ARBs) and in-hospital mortality of hypertensive patients diagnosed with Covid-19 pneumonia. Material and method In this retrospective study, we included 113 consecutive hypertensive patients admitted due to Covid-19 infection. In all patients, Covid-19 infection was confirmed with using reverse-transcription polymerase chain reaction. All patients were on ACE inh/ARBs or other antihypertensive therapy unless no contraindication was present. The primary outcome of the study was the in-hospital all-cause mortality. Results In total, 113 hypertensive Covid-19 patients were included, of them 74 patients were using ACE inh/ARBs. During in-hospital follow up, 30.9% [n = 35 patients] of patients died. The frequency of admission to the ICU and endotracheal intubation were significantly higher in patients using ACE inh/ARBs. In a multivariable analysis, the use of ACE inh/ARBs was an independent predictor of in-hospital mortality (OR: 3.66; 95%CI: 1.11–18.18; p= .032). Kaplan–Meir curve analysis displayed that patients on ACE inh/ARBs therapy had higher incidence of in-hospital death than those who were not. Conclusion The present study has found that the use of ACE inh/ARBs therapy might be associated with an increased in-hospital mortality in patients who were diagnosed with Covid-19 pneumonia. It is likely that ACE inh/ARBs therapy might not be beneficial in the subgroup of hypertensive Covid-19 patients despite the fact that there might be the possibility of some unmeasured residual confounders to affect the results of the study.